The Effect of Interval Training Methods on Aerobic Endurance in Soccer Playing Skills - Mochamad Zakky Mubarok; Riki Ramadhan; Nur Mahfuzah Agustin; Seni Oktriani; Dicky Oktora Mudzakir; Yudhi Kharisma; Fauzan Effendy (MASI Mandiri Edukasi, 2026)
The objectives of this study were: 1) To determine the effect of intensive and extensive interval training methods on improving soccer skills in the high and low aerobic endurance groups; 2) To determine the interaction between interval training methods and aerobic endurance on improving soccer skills. The study used an experimental method with a 2x2 factorial design. Participants were 28 soccer players from the West Java Zone 4 League. The soccer skills research instrument used the Game Performance Assessment Instrument (GPAI). Hypothesis testing was carried out using factorial analysis of variance (ANOVA). Based on the analysis of the research data processing and discussion, the following conclusions can be drawn from this study: 1) The application of intensive interval training methods has a better effect than the extensive interval training method in improving soccer skills in the high and low aerobic endurance groups; 2) There is no interaction between interval training methods and aerobic endurance in improving soccer skills. These findings suggest that intensive interval training is more effective regardless of aerobic endurance level.